ANALISIS NILAI TAMBAH DAN TINGKAT PRODUKTIVITAS KERJA SERTA STRATEGI PENGEMBANGAN HOME INDUSTRY GULA KELAPA DI DESA TEMBOKREJO KECAMATAN GUMUKMAS KABUPATEN JEMBER - Yohana Tyas Sulistiowati; Joni Murti Mulyo Aji; Rudi Hartadi (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Home industry of coconut sugar in Tembokrejo village processes palm sugar from sap. The purpose of this research is to know (1) Value added at home industry of coconut sugar in Tembokrejo village, (2) productivity level of home industry of coconut sugar in Tembokrejo village (3) strategy of coconut industry home development in Tembokrejo Village. Determination of research area is done intentionally (Purposive Method), that is in Tembokrejo Village District Gumukmas Jember Regency. The research method used is descriptive and analytical method, and sampling method used is Total Sampling. Methods of data collection using interview and observation techniques. The type of data used is primary data and secondary data. The analysis used is value-added analysis, work productivity analysis, SWOT and QSPM analysis. The results showed: (1) Value added on home indutry of coconut sugar in Tembokrejo village was Rp 1,637,04 / kg. (2) The productivity level of coconut industry home work is low ie Rp 5,858 / hour. (3) The development strategy of coconut sugar home industry is in White Area position. (4) QSPM obtained the priority of coconut industry home industry strategy with Total Attractiveness Score (TAS) value of 6,13 that is increasing coconut sugar production.